ACT-1 Multicenter investigator-initiated registration-directed Phase 2 study of E7090 in subjects with advanced or recurrent solid tumors with fibroblast growth factor receptor (FGFR) gene alteration: FORTUNE trial. (6th December 2021) - Takahashi, Masamichi; Chiba, Yohei; Sudo, Kazuki; Kojima, Yuki; Okuma, Hitomi; Kohsaka, Shinji; Ichimura, Masahiko; Okita, Natsuko; Nakamura, Kenichi; Machida, Ryunosuke; Kinoshita, Ichiro; Takahashi, Masanobu; et al.
Abstract: Background: Genetic alterations of FGFRs are known to play an important role in the proliferation, survival, and migration of cancer cells as well as tumor angiogenesis and drug resistance. E7090 is an orally available selective tyrosine kinase inhibitor for FGFR1-3. A global Phase 2 study of E7090 in subjects with unresectable advanced or metastatic cholangiocarcinoma harboring FGFR2 gene fusion is ongoing (NCT04238715). We recently reported FGFR alterations that are highly sensitive to E7090 using a high-throughput functional evaluation method called MANO method (Nakamura et al. npj Precision Oncology, 2021), narrowing down the most promising FGFR alteration targets. Here, we designed a single-arm, open-label, investigator-initiated multicenter Phase 2 basket study to evaluate the efficacy and safety of E7090 in subjects with advanced or recurrent solid tumors harboring FGFR gene alterations, focusing on alterations identified by MANO method, as a sub-study under the nationwide large registry for rare cancers in Japan (MASTER KEY Project). Methods: The key eligibility criteria are: 1) Histologically confirmed metastatic or locally advanced solid tumor; 2) Ineffective to or intolerant to first line treatment, or for which standard treatment is no longer available; and 3) Confirmed FGFR gene alterations via next-generation sequencing assays that are reimbursed by insurance. Subjects will receive E7090 140 mg orally once daily until disease progression or development of unacceptable toxicity. The primary endpoint is objective response rate (ORR) by independent central review (RECIST v1.1), and the secondary endpoints include ORR by investigator assessment, progression-free survival, overall survival, disease control rate, safety, duration of response, and time to response. For primary brain tumors, RANO criteria is also applied in assessment of response. The study enrolls approximately 45 subjects. (Clinical Trial Registry: jRCT2031210043, ClinicalTrials.gov: NCT04962867)